A Novel Model of Metastatic Conjunctival Melanoma in Immune-Competent Mice - Schlereth, Simona L.; Iden, Sandra; Mescher, Melina; Ksander, Bruce R.; Bosch, Jacobus J.; Cursiefen, Claus; Heindl, Ludwig M. (Investigative Ophthalmology & Visual Science, 2015)
Conjunctival melanoma (CM) is an ocular surface tumor that can lead to fatal metastases. Patients developing, tumor-associated lymphangiogenesis have a significantly increased risk of metastatic disease, because tumor spread primarily occurs via lymphatic vessels to the draining lymph node. Here, we describe a novel immune-competent mouse model of CM that displays tumor-associated lymphangiogenesis with development of metastatic tumors.C57BL/6N mice received C57BL/6N-derived dermal melanoma cells (hepatocyte growth factor [HGF] cyclin dependent kinase-4 [Cdk4]+) or B16F10 via subconjunctival injection. A clinical score quantified primary tumor growth and metastases were identified by macroscopic examination of the draining lymph nodes, lung, and spleen. Confirmation of tumors and metastases was achieved by immunohistochemical staining for markers of pigmented cells (tyrosinase related protein-2 [TRP2]) and S-100, and of cell proliferation (Ki67). The intra- and peritumoral CD31+ blood and lymphatic vessel endothelium hyaluronan receptor-1 (LYVE-1)+ lymphatic vessels were quantified immunohistochemically.All mice rapidly developed aggressive TRP2+, S100+, and Ki67+ CM. Metastatic tumors were found in the lymph node (9%) and lung (6%) of HGF-Cdk4(R24C)-treated mice and in the spleen (8%) and lung (17%) of B16F10-treated mice. The amount of peri- and intratumoral blood vessels was significantly increased compared with lymphatic vessels.This CM model in immune-competent animals offers new possibilities to study the pathobiology of tumor growth, invasion, and mechanisms of metastatic tumor spread, and provides a robust model to explore new immune-based and antilymphangiogenic treatment modalities of this malignancy.
EVALuna2:25719